Mindfulness and Levels of Stress: A Comparison of Beginner and Advanced Hatha Yoga Practitioners - Brisbon, Nicholas M. (Journal of religion and health, 2011)
The present study was designed to examine mindfulness and stress levels in beginner and advanced practitioners of Hatha Yoga. Participants (N = 52) were recruited through Hatha Yoga schools local to western Massachusetts. Beginner practitioners (n = 24) were designated as those with under 5 years (M = 3.33) experience and advanced practitioners (n = 28) as those with over 5 years (M = 14.53) experience in Hatha Yoga. The participants completed the Mindful Attention Awareness Scale (MAAS; Brown and Ryan 2003) and the Perceived Stress Scale (PSS; Cohen et al. 1983) directly preceding a regularly scheduled Hatha Yoga class. Based on two independent-samples t-tests, advanced participants scored significantly higher in mindfulness levels (P < .05) and significantly lower in stress levels (P < .05) when compared to beginner participants. Additionally, a significant negative correlation (r = -.45, P = .00) was found between mindfulness and stress levels. No significant correlations were found between experience levels and mindfulness and stress levels. Hatha Yoga may be an effective technique for enhancing mindfulness and decreasing stress levels in practitioners.